Celluloid Esther: the literary carnivalesque as transformed through the lens of the cinematic epic - McGeough, Kevin M. (Journal of the bible and its reception, 2017)
The reception of Esther has often been fraught with attempts to make the book more palatable to the audience receiving it and to interpret the book in a manner more consistent with the values of that community. This is evidence in cinematic adaptations of the book, where the story is transformed to better suit the genre expectations of the Biblical epic and the perspectives of the intended viewers. By examining two films based on Esther – Esther and the King (1960) and One Night with the King (2006) – some of the interpretive issues surrounding the tone and content of the Biblical source become apparent. If Esther is best understood as a carnivalesque work, as many scholars have suggested, then the expectations of this kind of work have not been met in the cinematic adaptations. Given the importance of film in contemporary Biblical reception, these new readings of Esther are perhaps particularly influential, at least within the restricted communities who view these movies. Likewise, analysis of these changes highlights the values of the makers of these films and the audiences who consume them.